Сучасний стан та шляхи удосконалення соціального забезпечення населення України - Криворучко, В. В.; Kryvoruchko, V. V. (Право і безпека. - 2013. - № 4 (51). - С. 128-132, 2013)
Вивчено місце соціального забезпечення у соціальній політиці держави. Обґрунтовано та визначено заходи, які необхідно вжити для поліпшення ситуації у сфері соціального забезпечення.

It is stated that the productive labor activity of people is a factor of country’s economic growth, welfare of workers and their families. Labor activity is always directed on creating material and spiritual goods, providing services, receiving income and other things. But there is an issue of distributing benefits to all members of the society in a state organized society including people who are not engaged in socially useful work by different reasons. Special attention is paid to the fact that the modern realities of Ukrainian society indicate a high level of unemployment, the great disparity in people’s incomes and poverty. The low level of pension guaranteeing for the vast majority of elderly and disabled people does not provide even the physiological minimum necessary for human survival, and the small sizes of many aids and inadequate social services, create an illusion of social guaranteeing. It is grounded that there is a need to realize the following main measures for improving the situation in the sphere of social guaranteeing. First, to develop and adopt the Code of Social Guaranteeing in Ukraine. Second, to develop and implement cumulative system of pension guaranteeing with appropriate state guarantees. Third, to make an inventory of all measures of population’s social guaranteeing in order to cancel those activities, which do not have a positive effect and are irrelevant to the subjects of their receipt and are burdening for the state. Fourth, to conduct benefits’ monetization, where it is possible.

Изучено место социального обеспечения в социальной политике государства. Обоснованы и определены мероприятия, которые необходимо провести для улучшения ситуации в сфере социального обеспечения.
Current status and ways to improve population’s social guaranteeing of Ukraine
Современное положение и пути усовершенствования социального обеспечения населения Украины
Keywords: соціальне забезпечення; соціальне обслуговування; соціальна політика; пенсія; соціальна допомога; безробіття; безробітний; social guaranteeing; social services; social policy; pension; social assistance; unemployment; unemployed person; социальное обеспечение; социальное обслуживание; социальная политика; пенсия; социальная помощь; безработица; безработный